Public health strategies for mass gathering events: A focus on the Milan–Cortina 2026 Olympic and paralympic winter games - Da Rech, Andrea; Marcotrigiano, Vincenzo; Voltolini, Anna; Manzi, Mattia; Fiorito, Nahuel; Battistin, Marica; Parpinel, Maria; Cinquetti, Sandro (Annali di Igiene Medicina Preventiva e di Comunità, 2026)
Introduction: Mass gatherings, such as the Milan–Cortina 2026 Olympic and Paralympic Winter Games, have potential implications for infectious diseases, food safety and environmental hygiene. In this setting, the Local Health Authority ULSS 1 Dolomiti has developed an integrated public health preparedness model that includes Cortina d’Ampezzo and its surrounding areas.Methods: An operational model was structured by the Prevention Department around three priority areas for intervention: (i) infectious diseases and epidemiological surveillance, including the implementation of syndromic and event-based systems by a dedicated public health team; (ii) food safety, with a strengthened programme of official controls and a shared food safety policy for business operators; and (iii) public health and environmental hygiene, including drinking water monitoring, Legionella spp. detection in tourist accommodation facilities, and developing a microbiological wastewater surveillance protocol (wastewater-based epidemiology).Results: Between January and August 2025,  44 inspections were carried out in food businesses, identifying non-compliance mainly in the areas of structural and hygiene/organizational issues and cleaning and sanitization procedures. From January 2024 to June 2025, 60 water samples were collected to verify compliance with potability requirements; a limited proportion of samples required follow-up investigations, with no formal non-compliance detected that exceeded the legal limits. The investigation of seven accommodation facilities included 26 samples for Legionella spp. screening; positive results—and thus the need to implement corrective actions—were found in three facilities.Conclusions: In light of the preliminary evidence arising from our investigation, Cortina d’Ampezzo’s pre-Olympic experience suggests that Olympic preparedness can strengthen local public health, enhancing legacy, prevention, coordination and response capacities among healthcare workers and the various institutions and organizations involved. The adoption of a preparedness model depicts a best practice for replication in other mass gathering settings, with potential long-term benefits for protecting public health and increasing the health system’s response capacity.